2016
DOI: 10.1111/nyas.13062
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake, nutritional status, and cognitive function with aging

Abstract: With the demographic aging of populations worldwide, diseases associated with aging are becoming more prevalent and costly to individuals, families, and healthcare systems. Among aging-related impairments, a decline in cognitive function is of particular concern, as it erodes memory and processing abilities and eventually leads to the need for institutionalized care. Accumulating evidence suggests that nutritional status is a key factor in the loss of cognitive abilities with aging. This is of tremendous impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 98 publications
(162 reference statements)
2
41
0
Order By: Relevance
“… 7 8 9 10 Conversely, when links between n3-PUFAs and individual component outcomes that help define healthy ageing have been studied, conflicting relations have been reported. For example, higher self reported estimates of dietary n3-PUFA and biomarker n3-PUFA levels are each inversely associated with the risk of cardiovascular disease, 11 12 13 fatal coronary heart disease in particular, 12 but can be associated with higher risk of prostate cancer, 14 15 with mixed or inconclusive findings for dietary or biomarker n3-PUFA levels and cancer, 14 15 16 17 18 19 20 21 22 23 diabetes, lung disease, chronic kidney disease, and cognitive and physical function. Thus, the relation of n3-PUFAs to overall healthy ageing in older adult populations is not well established.…”
Section: Introductionmentioning
confidence: 99%
“… 7 8 9 10 Conversely, when links between n3-PUFAs and individual component outcomes that help define healthy ageing have been studied, conflicting relations have been reported. For example, higher self reported estimates of dietary n3-PUFA and biomarker n3-PUFA levels are each inversely associated with the risk of cardiovascular disease, 11 12 13 fatal coronary heart disease in particular, 12 but can be associated with higher risk of prostate cancer, 14 15 with mixed or inconclusive findings for dietary or biomarker n3-PUFA levels and cancer, 14 15 16 17 18 19 20 21 22 23 diabetes, lung disease, chronic kidney disease, and cognitive and physical function. Thus, the relation of n3-PUFAs to overall healthy ageing in older adult populations is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated mean (95% CI) values of the MoCA‐J score according to the quartile of dietary hardness with or without adjustment for the following potential confounders: sex (men or women), area of residence (Western‐urban, Western‐rural, Eastern‐urban or Eastern‐rural), education (<10, 10‐12 or ≥13 years), frequency of going outdoors (<1, 1‐4 or ≥5 times per week), current smoking status (yes or no), alcohol consumption (yes or no), BMI (kg/m 2 , continuous), GDS‐5 depression score (continuous), hypertension (yes or no), diabetes (yes or no), medical history of cerebrovascular disease (yes or no) and ApoE‐ε4 allele carrier status (yes or no). In additional analyses, we further adjusted for intake of nutrients that may be protective against cognitive impairment, namely n‐3 polyunsaturated fatty acids (PUFA), antioxidants (vitamins A, E and C) and B vitamins (vitamins B 6 , B 12 and folate) (unit/1000 kcal, continuous). We calculated the unstandardised partial regression coefficients (95% CI) that reflect the change in MoCA‐J score per 100‐unit increase in dietary hardness.…”
Section: Methodsmentioning
confidence: 99%
“…The dramatic rise in the prevalence of cognitive decline and dementia in the ageing population has prompted widespread research efforts to identify potential modifiable factors . Diet is regarded as one of the most important modifiable factors affecting cognition . The potential protective effects of diet on risk of cognitive decline and dementia have been reported with regard to certain nutrients and foods such as fatty acids, antioxidant vitamins, B vitamins, fish, and fruit and vegetables, although epidemiological evidence regarding the association of these nutrients and foods with cognitive function is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The VDR is found in many cell types, including neurons and glial cells of the hippocampus, cortex and subcortical nuclei, which are essential for cognition 10,11 . Some studies have investigated the association between VitD levels and cognitive decline, and most of them showed that adequate levels of VitD are associated with anti-inflammatory and antioxidant action, induction of neurotransmitter gene expression, regulation of neurotrophic agents and Aβ clearance 10,12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%